Optimization of extraction process of plant-based gelatin replacer - Jaswir, Irwandi; Alotaibi, Abeer; Jamal, Parveen; Octavianti, Fitri; Lestari, Widya; Hendri, Ridar; Alkahtani, Ali Hussein (Universiti Putra Malaysia, 2016)
Gelatin is one of the most widely used food ingredients, with wide applications in the food industry. It was reported that 41% of the gelatin produced in the world is sourced from pig skin, 28.5% from bovine hides and 29.5% from bovine bones. However, factors such as the outbreak of BSE (a.k.a. mad cow disease) and increasing demand for non-mammalian gelatin for halal and kosher food markets have revived interest in gelatin replacers from plant sources. In this study, we have successfully extracted valuable pectin-as gelatin replacer--from various types of plant wastes. Pectin is a high value functional food ingredient widely used as a gelling agent and stabilizer. It is also an abundant, ubiquitous and multifunctional component of the cell walls of all land plants. Mango peel was screened as the ideal source for high-yield (36.6%) pectin of satisfactory quality. The results indicate that citric acid was the best solution for recovery of pectin from mango peels. An extraction temperature of 90°C and pH 2 provided the optimum conditions for maximum yield of pectin. The resulting crude mango peel pectin (CMPP) was analyzed for physicochemical parameters. The results indicated values for ash content (0.0412%), moisture content (0.303%), viscosity (45.18%), galacturonic acid content (36.8-37.2-40%) and degree of esterification (38.3-41%). Following analysis of its gelling properties and sensory evaluation, CMPP has good potential to be applied in the food industry as a low-methoxyl pectin and a cheap source of gelatin replacer for jam preparations. © All Rights Reserved.